High-regularity carbon microcrystalline petroleum coke, preparation method thereof, artificial graphite negative electrode material and preparation method of artificial graphite negative electrode material
Through the preparation of high-regular carbon microcrystalline petroleum coke and the preparation process of artificial graphite negative electrode materials, the problem of insufficient circulation and rate performance of the negative electrode materials of lithium-ion energy storage batteries is solved, and high-regular carbon microcrystalline petroleum coke and modifiers are realized The combination of the artificial graphite negative electrode material with excellent comprehensive performance was prepared, which meets the use needs of lithium-ion energy storage batteries.
Patent Information
- Application Number
- CN202310794523.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium-ion energy storage battery negative electrode material has limited circulation and rate performance, which cannot meet the needs of lithium-ion energy storage battery.
Using high-regular carbon microcrystalline petroleum coke as raw material, carbon microcrystalline petroleum coke with a high fine inlay structure ratio through cutting, decomposition, pyrolysis and polymerization, and mix it with a modifier for carbonization and graphitization to prepare Artificial graphite negative electrode material with excellent comprehensive performance.
It significantly improves the cycleability and rateability of the negative electrode material of lithium-ion energy storage battery, meets the needs of the negative electrode material of lithium-ion energy storage battery, and extends the battery service life.
Smart Images

Figure CN119220284A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphite negative electrode materials, and relates to a highly regular carbon microcrystalline petroleum coke and a preparation method thereof, an artificial graphite negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries can be divided into energy storage, power and consumer batteries according to their application areas. Energy storage batteries cover communication energy storage, power energy storage, distributed energy systems, etc., and are important energy systems that support the energy Internet. In recent years, in order to cope with the year-on-year growth in my country's electricity demand, as well as the increasingly serious problems of the grid-connected new energy sources such as wind, hydro, and solar power, and the increasing dispatching pressure of the power grid system, my country has continued to reform the power system, promote the construction of intelligent power grids, and vigorously introduce energy storage technologies to cope with the problems of outdated power systems, insufficient supply of electricity, and increasingly severe peak-shaving problems of power grids.
[0003] In electrochemical energy storage systems, battery energy storage technology uses the conversion between electrical energy and chemical energy to achieve the storage and output of electrical energy. It not only has the technical characteristics of rapid response and two-way regulation, but also has the technical advantages of strong environmental adaptability, small-scale decentralized configuration and short construction period. Among them, lithium-ion battery energy storage systems have flourished in the power industry of countries around the world due to their significant advantages such as high energy density, large discharge rate, and continuously declining costs. Lithium-ion energy storage batteries require that the negative electrode materials have high structural consistency, rate, and cyclicity, and at the same time hope to have low costs. The carbon materials used to make negative electrode materials for lithium-ion batteries are mainly divided into two categories, namely artificial graphite and natural graphite. The natural graphite negative electrode omits the graphitization process and is relatively cheap, but its cyclicity and consistency are not as good as artificial graphite, and the price of artificial graphite is relatively high. Therefore, how to further improve its comprehensive performance such as cyclicity and rate on the basis of reducing the cost of artificial graphite negative electrode materials to meet the use needs of negative electrode materials for lithium-ion energy storage batteries is a technical problem that needs to be solved urgently.
[0004] In response to the above problems, Chinese patent document CN114744149A discloses a negative electrode sheet with a double-layer active material layer. By adjusting the interlayer spacing of the negative electrode active material, a large interlayer spacing is used to improve the cycle performance and rate performance of the battery, and a small interlayer spacing is used to compensate for the loss of battery volume energy density caused by the large interlayer spacing. The two cooperate with each other to achieve the improvement of the cycle performance and rate performance of the battery without losing the volume energy density of the battery. At the same time, the expansion and dynamics are also improved to a certain extent. The negative electrode material is selected from any one of soft carbon, hard carbon, artificial graphite, and natural graphite. However, this method has limited improvement on the cycle performance and rate performance of the battery.
[0005] Chinese patent document CN114933301 discloses a method for preparing an artificial graphite negative electrode material, specifically, a mixture of any one or two of petroleum asphalt, coal tar asphalt, and natural asphalt with a softening point of 60°C to 90°C, and crushed coke powder such as low-sulfur petroleum coke, asphalt coke, coal coke, and metallurgical coke, kneading, cold isostatic pressing, hot carbonization treatment, graphitization, and then acid purification to obtain a long-life artificial graphite negative electrode material for energy storage. However, the use of asphalt with a lower softening point and coke powder kneading after carbonization will form a large number of pores, thereby forming a higher specific surface area and a lower first efficiency. More defect sites will also bring about problems such as possible poor cyclicity, and acid washing and purification after graphitization greatly increase the difficulty of removing impurities.
[0006] Chinese patent document CN109735361A discloses a method for preparing high microscopic strength mosaic structure asphalt coke, which specifically uses heavy asphalt as raw material, undergoes oxidative polymerization treatment, and then undergoes deep polycondensation to obtain high microscopic strength mosaic structure asphalt coke. Chinese patent document CN108251143A discloses using tar distillation distillation tower bottom asphalt and heavy oil to prepare soft asphalt, which is heated in a coking tower for carbonization cracking and condensation reaction to obtain asphalt coke. The above two schemes mainly use heavy asphalt and untreated medium-temperature asphalt as raw materials, and the final negative electrode material has a low energy density.
[0007] Chinese patent document CN116053424A discloses a method for preparing negative electrode materials for lithium-ion batteries, wherein heavy fraction oil is firstly used to obtain granulated asphalt by pressurized thermal polycondensation, and then carbonaceous raw materials (needle coke, petroleum coke and natural graphite, etc.) are crushed to a D50 of 5 to 20 μm and then mixed with the granulated asphalt, treated at a high temperature of 700 to 1100°C in an inert gas, graphitized at 2200 to 3000°C, and cooled to obtain negative electrode materials. However, the cycle performance of the negative electrode material needs to be improved.
[0008] In summary, the existing improvement methods have limited effect on improving the comprehensive performance of negative electrode materials such as cyclability, and cannot meet the use requirements of negative electrode materials for lithium-ion energy storage batteries. Summary of the invention
[0009] Based on the problems existing in the prior art and the directions for improvement, the present invention provides a high-order carbon microcrystalline petroleum coke and a preparation method thereof. The high-order carbon microcrystalline petroleum coke fundamentally solves the problem that the negative electrode materials made from existing petroleum coke or asphalt coke cannot meet the use requirements of negative electrode materials for lithium-ion energy storage batteries, especially the problem of cycle performance.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] A high-order carbon microcrystalline petroleum coke, wherein the fine mosaic structure ratio of the high-order carbon microcrystalline petroleum coke is greater than or equal to 90%; the carbon microcrystalline structure size is 1 to 10 μm, concentrated in 3 to 8 μm; the volatile matter content is 5% to 15%, preferably 8% to 12%; the true density is 1.4 to 1.6 g / cm 3 ; The ash content is 0.01% to 0.02%; the sulfur content is 0.5% to 1%.
[0012] The present invention also provides a method for preparing the above-mentioned high-regular carbon microcrystalline petroleum coke, comprising the following steps:
[0013] Cutting: Cutting the light oil from the crude oil to get the heavy oil;
[0014] Impurity removal: passing the heavy oil into a composite flow field of an electrostatic field and a gravity field for purification to obtain a high-regular carbon microcrystalline petroleum coke precursor raw material;
[0015] Pyrolysis: Under stirring, the high-order carbon microcrystalline petroleum coke precursor raw material is subjected to pyrolysis reaction with oxygen-containing gas to obtain a high-order carbon microcrystalline petroleum coke precursor;
[0016] Polymerization: The precursor of the high-regular carbon microcrystalline petroleum coke is thermally mixed with the carbonaceous micropowder, and the obtained mixture is subjected to polymerization reaction to obtain the high-regular carbon microcrystalline petroleum coke.
[0017] Optionally, in the preparation method of high-structured carbon microcrystalline petroleum coke provided by the present invention, the raw oil is selected from at least one of catalytic cracking slurry, ethylene tar, coker wax oil, thermal cracking residue, hydrogenation tail oil, furfural extraction oil, reforming heavy aromatic oil, ester refining solvent extraction lubricating oil and deasphalted oil of vacuum residue. Among them, catalytic cracking slurry refers to distillate oil obtained by catalytic cracking unit, and the catalytic cracking unit processes heavy distillate oil obtained by processing naphthenic crude oil, heavy distillate oil obtained by processing paraffinic crude oil, and heavy distillate oil obtained by processing intermediate base crude oil.
[0018] Optionally, in the method for preparing highly regular carbon microcrystalline petroleum coke provided by the present invention, in the cutting step, the light oil is distilled and cut off at 0.6 to 2.7 kPa, and the initial distillation point of the heavy oil is 240 to 350°C, preferably 250 to 340°C, and more preferably 260 to 330°C.
[0019] Optionally, in the method for preparing high-regular carbon microcrystalline petroleum coke provided by the present invention, in the cutting step, the density of the heavy oil obtained at 15°C is 0.9-1.1 g / cm 3; The asphaltene content is 0-20%, the gum content is 0-18%, the aromatic content is 60%-90%, the saturated content is 10%-30%, the sulfur content is 0.1%-2%, the nitrogen content is 0.1%-1%, and the ash content is 100-2000ppm.
[0020] Optionally, in the method for preparing high-order carbon microcrystalline petroleum coke provided by the present invention, in the impurity removal step, particles and particles of various sizes in the heavy oil are attracted to the surface of the filler by the dielectrophoretic force and gravity through the composite flow field of the electrostatic field and the gravity field, and are removed to obtain the high-order carbon microcrystalline petroleum coke precursor raw material; the intensity of the electrostatic field is 1×10 5 ~10×10 5 V / m, preferably 2×10 5 ~8×10 5 V / m;
[0021] The flow rate of the heavy oil passing into the composite flow field of the electrostatic field and the gravity field is 0.0001-0.001 m / s, preferably 0.0005-0.0008 m / s.
[0022] Optionally, in the method for preparing high-structured carbon microcrystalline petroleum coke provided by the present invention, the high-structured carbon microcrystalline petroleum coke precursor raw material obtained in the impurity removal step has an asphaltene content of 0 to 5% and an ash content of 0 to 5 ppm.
[0023] In the preparation method of the highly regular carbon microcrystalline petroleum coke precursor provided by the present invention, the pyrolysis reaction is carried out in an electromagnetic heating device with stirring. The specific electromagnetic heating device can be a kettle type or a tubular type. The tubular reactor controls the reaction process by controlling the time for the material to pass through the reactor or the retention time in the reactor.
[0024] Optionally, in the method for preparing high-structured carbon microcrystalline petroleum coke provided by the present invention, in the pyrolysis step, the mass volume ratio of the high-structured carbon microcrystalline petroleum coke precursor raw material to the oxygen-containing gas is 1kg:(0.2-2)L, preferably 1kg:(0.5-1.5)L; the temperature of the oxygen-containing gas is 100-300°C, preferably 150-250°C;
[0025] The oxygen-containing gas is selected from air, oxygen, or a mixture of oxygen and an inert gas; the inert gas is nitrogen, argon or helium. More preferably, the oxygen-containing gas is a mixture of oxygen and an inert gas, and the volume ratio of the oxygen to the inert gas in the mixture of oxygen and an inert gas is 1:3 to 1:5;
[0026] The temperature of the pyrolysis reaction is 280-380°C, preferably 300-320°C; the pyrolysis reaction time is 1-10h, preferably 3-5h; the stirring rate is 50-200r / min, preferably 100-150r / min; the heating rate is 10-30°C / min, preferably 15-25°C / min.
[0027] Optionally, in the method for preparing high-regular carbon microcrystalline petroleum coke provided by the present invention, in the pyrolysis step, the high-regular carbon microcrystalline petroleum coke precursor raw material is mixed with an oxygen-containing gas at 100 to 200° C. (preferably 120 to 170° C.) and then subjected to a pyrolysis reaction.
[0028] Optionally, in the method for preparing high-structured carbon microcrystalline petroleum coke provided by the present invention, the initial boiling point of the precursor of the high-structured carbon microcrystalline petroleum coke obtained in the pyrolysis step is 360-420°C, preferably 380-400°C; the density at 100°C is 1.1-1.3 g / cm 3 ; Asphaltene content is 1% to 20%, gum content is 1% to 20%, aromatic content is 50% to 70%; saturated content is 1% to 5%; residual carbon content is 20% to 30%, preferably 22% to 25%; aromatic hydrogen content is 10% to 25%, preferably 15% to 20%.
[0029] Optionally, in the method for preparing high-regular carbon microcrystalline petroleum coke provided by the present invention, in the polymerization step, the mass ratio of the precursor of the high-regular carbon microcrystalline petroleum coke to the carbonaceous micropowder is 100:1 to 100:20, preferably 100:5 to 100:10;
[0030] The carbonaceous powder is selected from at least one of needle coke powder, pitch coke powder, isotropic coke powder, artificial graphite powder and fine powder produced in the process of preparing artificial graphite; the carbonaceous powder has a particle size of less than 5um, preferably less than 3um, and more preferably less than 2um;
[0031] The polymerization reaction temperature is 450-550°C, and the reaction time is 5-36h, preferably 12-24h;
[0032] The heat mixing method is a pipeline mixer, preferably a kneader or a screw extruder; the heat mixing time is 30 to 60 minutes.
[0033] The present invention also provides a method for preparing an artificial graphite negative electrode material, comprising the following steps:
[0034] Crushing: crushing the high-order carbon microcrystalline petroleum coke and the modifier separately;
[0035] Mixing modification: After the above-mentioned crushed high-regular carbon microcrystalline petroleum coke is mixed with the crushed modifier, surface modification is performed in an oxygen-containing nitrogen atmosphere to obtain a modified material;
[0036] Heat treatment: the modified material is subjected to carbonization and graphitization treatment in an inert atmosphere (such as nitrogen, helium or argon) in sequence to obtain an artificial graphite negative electrode material;
[0037] Wherein, the high-order carbon microcrystalline petroleum coke is the high-order carbon microcrystalline petroleum coke mentioned above or the high-order carbon microcrystalline petroleum coke prepared by the preparation method of the high-order carbon microcrystalline petroleum coke mentioned above.
[0038] Optionally, in the method for preparing the artificial graphite negative electrode material provided by the present invention, the D10 of the crushed high-regular carbon microcrystalline petroleum coke is 1 to 5 um, preferably 2 to 4 um; the D90 is 9 to 15 um, preferably 10 to 12 um; and the D50 is 5 to 8 um, preferably 6 to 7 um;
[0039] The modifier is petroleum asphalt or coal-based asphalt powder with a softening point greater than 150°C, and the mass ratio of the crushed high-regular carbon microcrystalline petroleum coke to the modifier is 100:1 to 100:15, preferably 100:7 to 100:9;
[0040] The mixing time of the crushed high-regular carbon microcrystalline petroleum coke and the crushed modifier is 30 to 60 minutes, preferably 40 to 50 minutes.
[0041] Optionally, in the method for preparing the artificial graphite negative electrode material provided by the present invention, the oxygen-containing nitrogen atmosphere is a mixed gas of a gas containing oxygen elements and nitrogen, the volume ratio of the gas containing oxygen elements to the nitrogen is 1 to 10:100, preferably 4 to 6:100, the gas containing oxygen elements is selected from water vapor, carbon dioxide, air or a mixture of pure oxygen and an inert gas, and the inert gas is selected from nitrogen, helium or argon;
[0042] During the surface modification process, the flow rate of the oxygen-containing nitrogen is 0.01 to 0.3 L / min, preferably 0.05 to 0.1 L / min, the surface modification temperature is 550 to 700°C, preferably 620 to 670°C; the surface modification time is 5 to 15 h, preferably 6 to 10 h, and the heating rate is 1 to 10°C / min, preferably 5 to 7°C / min.
[0043] Optionally, in the method for preparing the artificial graphite negative electrode material provided by the present invention, the surface modification is carried out under stirring or rolling state; after the surface modification is completed, nitrogen is introduced and cooled to room temperature to obtain the modified material.
[0044] Optionally, in the method for preparing the artificial graphite negative electrode material provided by the present invention, the carbonization temperature is 800-1100°C, and the graphitization temperature is 2700-3000°C.
[0045] The present invention also provides an artificial graphite negative electrode material obtained by the preparation method of the above-mentioned artificial graphite negative electrode material, wherein the D50 of the artificial graphite negative electrode material is 10 to 22 um, preferably 12 to 18 um.
[0046] The present invention also provides a lithium ion battery, comprising the artificial graphite negative electrode material prepared by the preparation method of the artificial graphite negative electrode material.
[0047] Compared with the prior art, the present invention has the following advantages:
[0048] 1. In view of the problem that the existing methods for improving negative electrode materials have limited improvement on the comprehensive performance of lithium batteries such as circulation, and cannot meet the use requirements of negative electrode materials for lithium-ion energy storage batteries, the inventors have broken through the existing research and development limitations and made improvements starting from the source raw materials for preparing negative electrode materials and the essence of the long-cycle performance of lithium battery negative electrode materials, fundamentally improving the comprehensive performance of negative electrode materials such as cyclability, which can meet the use requirements of negative electrode materials for lithium-ion energy storage batteries.
[0049] Most of the artificial graphite materials used in existing energy storage lithium batteries are prepared from asphalt coke or petroleum coke as raw materials. Their microstructures are composed of streamlined fiber structures, sheet structures, and mosaic structures of varying sizes. The proportions of various structures fluctuate and are inconsistent due to the selection of raw materials and different process conditions, which affects the uniformity of the properties of artificial graphite and the performance of energy storage lithium batteries, or cannot be used for the manufacture of large-scale energy storage lithium batteries. Therefore, the inventors believe that improving the consistency of the microstructure of asphalt coke or petroleum coke is the key to ensuring the uniformity of the properties of artificial graphite and the performance of energy storage lithium batteries. Isotropic coke is usually prepared by doping elements such as nitrogen or using heavy coal tar pitch. Due to the high content of impurity elements and metals, lattice defects will be introduced after later heat treatment or graphitization, affecting the performance of capacity, and will also bring certain environmental problems. The use of petroleum raw materials is easy to form a streamlined structure due to the high molecular fluidity, so it is difficult to obtain petroleum coke with isotropic structure.
[0050] Based on the above innovative thinking, the inventors provide a highly regular carbon microcrystalline petroleum coke, wherein the fine mosaic structure ratio is greater than 90%; the carbon microcrystalline structure size is 1 to 10 μm, concentrated in 3 to 8 μm; the volatile content is 5% to 15%, preferably 8% to 12%; the true density is 1.4 to 1.6 g / cm 3; The ash content is 0.001% to 0.02%; the sulfur content is 0.5% to 1%. By adopting the specific preparation process of high-regular carbon microcrystalline petroleum coke combined with artificial graphite, the lithium battery negative electrode material has excellent comprehensive properties such as long-life energy storage and rate capability.
[0051] 2. The preparation of high-regular carbon microcrystalline petroleum coke is a difficult point in the research of this field. From the perspective of the design of the reaction principle of the mesophase theory, when the impurities in the heavy components of petroleum are removed and the content is low, the condensed aromatic molecules are easy to form large-sized carbon microcrystals, and then produce and develop into large-scale crystal structures, and cannot generate small-sized and uniform mosaic structures. When the non-carbon elements such as metals and non-metallic elements in the raw materials are high, the generated petroleum coke cannot obtain a more satisfactory battery capacity after subsequent heat treatment and graphitization, and the key is that the service life is short. However, this type of petroleum coke is crucial to the performance of negative electrode materials such as energy storage life. After in-depth research and creative practice, the inventors finally used petroleum raw materials such as catalytic cracking oil slurry, ethylene tar, etc. as raw materials, cut to remove light oil, and then remove impurities to obtain a high-regular carbon microcrystalline petroleum coke precursor raw material, and then perform aromatic molecular design (pyrolysis), combined with adjusting the size and distribution of the microcrystalline structure of the coke (polymerization after hot mixing with carbon-containing micropowder), and the mutual cooperation between the steps, finally obtained a petroleum coke with high regular carbon microcrystalline.
[0052] 3. The preparation method of the artificial graphite negative electrode material provided by the present invention comprises crushing the high-regular carbon microcrystalline petroleum coke and the modifier respectively, mixing them, and then carbonizing and graphitizing them to obtain the artificial graphite negative electrode material. The preparation process is simple, low-cost, suitable for energy storage batteries, prolonging the battery life, and used for long-life energy storage lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a polarized photo of the highly regular carbon microcrystalline petroleum coke prepared in Example 1 of the present invention;
[0054] Figure 2 This is a polarized photo of the highly regular carbon microcrystalline petroleum coke prepared in Example 2 of the present invention;
[0055] Figure 3 This is a polarized photo of the petroleum coke prepared in Comparative Example 1 of the present invention;
[0056] Figure 4 This is a polarized photograph of the petroleum coke prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0057] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.
[0058] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0059] Test method 1: Mix the artificial graphite negative electrode material with carboxymethyl cellulose, conductive carbon black, and styrene-butadiene rubber in a mass ratio of 95%:1.5%:1.5%:2% to make a slurry, and then coat it on a 12μm thick copper foil. The surface density of the negative electrode sheet is 80g / m 2 The compaction density of roller pressing is 1.56g / cm 3 The rolled negative electrode sheet was punched into 8.4 mm negative electrode sheets and assembled into CR2016 button-type half-cells in a glove box. The counter electrode was a lithium sheet for the test of specific capacity and initial efficiency.
[0060] Test method 2: Mix NCM523 material with polyvinylidene fluoride, conductive carbon black, and carbon nanotube conductive liquid in a mass ratio of 97%: 1.2%: 1.5%: 0.3% to make a slurry, and then coat it on a 25μm thick aluminum foil. The surface density of the positive electrode sheet is 170g / m 2 The compaction density of the roller is 3.4g / cm 3 . The 5.1cm×3.1cm negative electrode sheet and the 5.0cm×3.0cm positive electrode sheet were assembled into a soft pack battery (capacity ~38mAh) after the tab welding, lamination, baking, injection and sealing processes for the test of cycle performance. The charge and discharge current is 1C / 1C. The battery assembly uses 1mol / LLiPF6 electrolyte [EC∶EMC∶DEC is 3∶5∶2 (mass ratio), 2.5% (mass fraction) FEC, a small amount of PS, DTD and LITFSI].
[0061] Example 1
[0062] This embodiment provides a highly regular carbon microcrystalline petroleum coke and artificial graphite negative electrode material, and the specific steps are as follows:
[0063] Preparation of Highly Regular Carbon Microcrystalline Petroleum Coke
[0064] Cutting: Ethylene tar, catalytic cracking oil slurry and petroleum residue were mixed in a mass ratio of 70:20:10, and then vacuum distilled at a pressure of 1.33 kPa to remove light oil and collect heavy oil with an initial boiling point of 300°C. After testing, the density of the heavy oil at 15°C was 1.05 g / cm 3 , asphaltene content is 14%, resin content is 10%, aromatic content is 70%, saturated content is 25%, sulfur content is 1%, nitrogen content is 0.2%, and ash content is 500ppm.
[0065] Impurity removal: The heavy oil is passed through a composite flow field of electrostatic field and gravity field for purification and impurity removal. The intensity of the electrostatic field is 5×10 5 V / m, the flow rate of heavy oil passing into the composite flow field is 0.0005m / s, and a high-regular carbon microcrystalline petroleum coke precursor raw material is obtained. The asphaltene content is 4% and the ash content is 5ppm.
[0066] Pyrolysis: The above-mentioned high-order carbon microcrystalline petroleum coke precursor raw material is input into a stirring electromagnetic heating reactor, and heated at a stirring rate of 150r / min from room temperature at a heating rate of 20℃ / min, and 100℃ air is introduced at the same time (the volume mass ratio of air to high-order carbon microcrystalline petroleum coke precursor raw material is controlled to be 1L:1Kg). After pyrolysis reaction at 320℃ for 5h, a high-order carbon microcrystalline petroleum coke precursor with a yield of 71% is obtained. After testing, the initial distillation point of the high-order carbon microcrystalline petroleum coke precursor is 380℃, and the density at 100℃ is 1.12g / cm 3 , asphaltene content is 20%, resin content is 19%, aromatic content is 60%, saturated content is 1%, residual carbon content is 25%, and aromatic hydrogen content is 15%.
[0067] Polymerization: The precursor of high-regular carbon microcrystalline petroleum coke and the same type of coke powder with a particle size of less than 2um are hot mixed in a screw extruder at a mass ratio of 100:10 for 40 minutes. The obtained mixture is transported to a kettle polymerization reactor by a high-temperature mechanical pump for polymerization reaction at 510°C for 24 hours, and then cooled to room temperature to obtain high-regular carbon microcrystalline petroleum coke. According to the test, the fine mosaic structure ratio of the high-regular carbon microcrystalline petroleum coke is 93%, the carbon microcrystalline structure size is 1 to 10um, and the concentrated distribution is 4 to 7um; the volatile matter is 8%, and the true density is 1.52g / cm 3 , the ash content is 0.005% and the sulfur content is 0.5%.
[0068] Preparation of artificial graphite
[0069] Crushing: High-order carbon microcrystalline petroleum coke and petroleum asphalt (softening point is 200°C) are crushed and classified by mechanical grinding machines to obtain high-order carbon microcrystalline petroleum coke powder and petroleum asphalt powder. The D10, D90 and D50 of the high-order carbon microcrystalline petroleum coke powder are 3um, 11um and 7um respectively.
[0070] Mixing modification: High-regular carbon microcrystalline petroleum coke powder and petroleum asphalt powder are mixed in a conical mixer at a mass ratio of 100:7 for 50 minutes, and then heated to 650°C at a rate of 10°C / min in a reactor containing a stirring device. The coke powder surface is modified at this temperature in a mixed atmosphere of air and nitrogen (the volume ratio of air to nitrogen is 5:100, and the flow rate is 0.09L / min) for 10 hours, and then nitrogen is introduced for cooling to room temperature to obtain a modified material;
[0071] Heat treatment (carbonization + graphitization): The modified material is carbonized at 1000°C and graphitized at 2800°C in a nitrogen atmosphere, and then crushed, classified, demagnetized and screened to obtain an artificial graphite negative electrode material.
[0072] Example 2
[0073] This embodiment provides a highly regular carbon microcrystalline petroleum coke and artificial graphite negative electrode material, and the specific steps are as follows:
[0074] Preparation of Highly Regular Carbon Microcrystalline Petroleum Coke
[0075] Cutting: Ethylene tar, reformed heavy aromatic oil and thermal cracking residue oil were mixed in a mass ratio of 65:25:10, and then vacuum distilled at a pressure of 2.66 kPa to remove light oil and collect heavy oil with an initial distillation point of 250°C. After testing, the density of the heavy oil at 15°C is 0.95 g / cm 3 , asphaltene content is 10%, resin content is 8%, aromatic content is 65%, saturated content is 17%, sulfur content is 0.7%, nitrogen content is 0.1%, and ash content is 700ppm.
[0076] Impurity removal: The heavy oil is passed through a composite flow field of electrostatic field and gravity field for purification and impurity removal. The intensity of the electrostatic field is 7×10 5 V / m, the flow rate of heavy oil into the composite was 0.0005m / s, and the obtained high-regular carbon microcrystalline petroleum coke precursor raw material had an asphaltene content of 3% and an ash content of 4ppm after testing.
[0077] Pyrolysis: The above-mentioned high-order carbon microcrystalline petroleum coke precursor raw material is input into a stirring electromagnetic heating reactor, and heated at a stirring rate of 100r / min from room temperature at a heating rate of 10℃ / min, and 150℃ air is introduced at the same time (the volume mass ratio of air to high-order carbon microcrystalline petroleum coke precursor raw material is controlled to be 1L:1Kg). After pyrolysis reaction at 320℃ for 9h, a high-order carbon microcrystalline petroleum coke precursor with a yield of 79% is obtained. After testing, the initial distillation point of the high-order carbon microcrystalline petroleum coke precursor is 400℃, and the density at 100℃ is 1.15g / cm 3 , asphaltene content is 16%, resin content is 18%, aromatic content is 64%, saturated content is 2%, residual carbon content is 22%, and aromatic hydrogen content is 24%.
[0078] Polymerization: The precursor of high-regular carbon microcrystalline petroleum coke and needle coke powder with a particle size of less than 2um are hot mixed in a screw extruder at a mass ratio of 100:2 for 50 minutes. The obtained mixture is transported to a polymerization reactor by a high-temperature mechanical pump for polymerization reaction at 450°C for 10 hours, and then cooled to room temperature to obtain high-regular carbon microcrystalline petroleum coke. According to the test, the fine mosaic structure ratio of the high-regular carbon microcrystalline petroleum coke is 96%, the carbon microcrystalline structure size is 1 to 10um, and the concentrated distribution is 5 to 8um; the volatile matter is 15%, and the true density is 1.59g / cm 3 , the ash content is 0.01% and the sulfur content is 0.7%.
[0079] Preparation of Highly Regular Carbon Microcrystalline Petroleum Coke
[0080] Crushing: High-order carbon microcrystalline petroleum coke and petroleum asphalt (softening point is 200°C) are crushed and classified by mechanical grinding machines to obtain high-order carbon microcrystalline petroleum coke powder and petroleum asphalt powder. The D10, D90 and D50 of the high-order carbon microcrystalline petroleum coke powder are 3um, 11um and 5um respectively.
[0081] Mixing modification: The crushed high-regular carbon microcrystalline petroleum coke powder and petroleum asphalt powder are mixed in a conical mixer at a mass ratio of 100:7 for 50 minutes, and then heated to 650°C at a rate of 1°C / min in a reactor containing a stirring device. The coke powder surface is modified at this temperature in a mixed atmosphere of air and nitrogen (the volume ratio of air to nitrogen is 3:100, and the flow rate is 0.1L / min) for 5 hours, and then nitrogen is introduced for cooling to room temperature to obtain a modified material;
[0082] Heat treatment (carbonization + graphitization): The modified material is carbonized at 1000°C and graphitized at 2800°C in a nitrogen atmosphere, and then broken up, classified, demagnetized and screened to obtain an artificial graphite negative electrode material.
[0083] Example 3
[0084] This embodiment provides a preparation method of a highly regular carbon microcrystalline petroleum coke and artificial graphite negative electrode material, and the specific steps are as follows:
[0085] Highly structured carbon microcrystalline petroleum coke
[0086] Cutting: Ethylene tar, reforming heavy aromatic oil and ethylene hydrogenation tail oil were mixed in a mass ratio of 10:15:75, and then vacuum distilled at a pressure of 0.66 kPa to remove light oil and collect heavy oil with an initial distillation point of 350 ° C; after testing, the density of the heavy oil at 15 ° C was 0.91 g / cm 3 , asphaltene content is 3%, resin content is 1%, saturated content is 30%, aromatic content is 65%, sulfur content is 0.1%, nitrogen content is 0.5%, and ash content is 800ppm.
[0087] Impurity removal: The heavy oil is passed through a composite flow field of electrostatic field and gravity field for purification and impurity removal. The intensity of the electrostatic field is 5×10 5 V / m, the flow rate of heavy oil into the composite was 0.001m / s, and the obtained high-regular carbon microcrystalline petroleum coke precursor raw material had an asphaltene content of 2% and an ash content of 3ppm after testing.
[0088] Pyrolysis: The above-mentioned high-regular carbon microcrystalline petroleum coke precursor raw material is input into a stirring electromagnetic heating reactor, and heated from room temperature at a heating rate of 30°C / min at a stirring rate of 50r / min, and a mixed gas of 200°C oxygen and nitrogen (the volume ratio of oxygen to nitrogen is 1:5) is introduced (the volume mass ratio of air to high-regular carbon microcrystalline petroleum coke precursor raw material is controlled to be 1L:1Kg), and after pyrolysis reaction at 350°C for 4h, a high-regular carbon microcrystalline petroleum coke precursor with a yield of 62% is obtained; after testing, the initial distillation point of the high-regular carbon microcrystalline petroleum coke precursor is 382°C, and the density at 100°C is 1.23g / cm 3 , asphaltene content is 18%, resin content is 20%, aromatic content is 58%, saturated content is 4%, residual carbon content is 29%, and aromatic hydrogen content is 23%.
[0089] Polymerization: The high-order carbon microcrystalline petroleum coke precursor and artificial graphite powder with a particle size of less than 1um are hot mixed in a screw extruder at a mass ratio of 100:20 for 30 minutes. The obtained mixture is transported to a polymerization reactor by a high-temperature mechanical pump for polymerization reaction at 550°C for 5 hours, and then cooled to room temperature to obtain high-order carbon microcrystalline petroleum coke. According to the test, the fine mosaic structure ratio of the high-order carbon microcrystalline petroleum coke is 95%, the carbon microcrystalline structure size is 1 to 10um, and the concentrated distribution is 3 to 5um; the volatile matter is 5%, and the true density is 1.4g / cm 3, the ash content is 0.001% and the sulfur content is 0.5%.
[0090] Artificial graphite preparation
[0091] Crushing: High-order carbon microcrystalline petroleum coke and petroleum asphalt powder (softening point is 180°C) are crushed and classified by a mechanical grinder to obtain high-order carbon microcrystalline petroleum coke powder and petroleum asphalt powder, wherein the D10, D90 and D50 of the crushed high-order carbon microcrystalline petroleum coke are 5um, 15um and 8um respectively;
[0092] Mixing modification: High-regular carbon microcrystalline petroleum coke powder and petroleum asphalt powder are mixed in a conical mixer at a mass ratio of 100:9 for 30 minutes, and then heated to 670°C at a rate of 2°C / min in a reactor containing a stirring device. The surface of the coke powder is modified at this temperature in a mixed atmosphere of carbon dioxide and nitrogen (the volume ratio of carbon dioxide to nitrogen is 10:100, and the flow rate is 0.05L / min) for 5 hours, and then nitrogen is introduced for cooling to room temperature to obtain a modified material;
[0093] Heat treatment (carbonization + graphitization): The modified material is carbonized at 1000°C and graphitized at 2800°C in a nitrogen atmosphere, and then crushed, classified, demagnetized and screened to obtain an artificial graphite negative electrode material.
[0094] Example 4
[0095] Preparation of Highly Regular Carbon Microcrystalline Petroleum Coke
[0096] Cutting: Mix the de-oiled asphalt of vacuum residue, catalytic cracking oil slurry and ethylene tar in a mass ratio of 30:20:50, and then perform vacuum distillation at a pressure of 0.6 kPa to remove the light oil and collect the heavy oil with an initial distillation point of 340°C. After testing, the density of the heavy oil at 15°C is 1.09 g / cm 3 , asphaltene content is 20%, resin content is 18%, aromatic content is 52%, saturated content is 10%, sulfur content is 1%, nitrogen content is 0.3%, and ash content is 1200ppm.
[0097] Impurity removal: The heavy oil is passed through a composite flow field of electrostatic field and gravity field for purification and impurity removal. The intensity of the electrostatic field is 10×10 5 V / m, the flow rate of heavy oil passing into the composite flow field is 0.0007m / s, and a high-regular carbon microcrystalline petroleum coke precursor raw material is obtained. The asphaltene content is 4% and the ash content is 5ppm.
[0098] Pyrolysis: The above-mentioned high-order carbon microcrystalline petroleum coke precursor raw material is input into a stirring electromagnetic heating reactor, and heated at a stirring rate of 200r / min from room temperature at a heating rate of 30℃ / min, and 100℃ air is introduced at the same time (the volume mass ratio of air to high-order carbon microcrystalline petroleum coke precursor raw material is controlled to be 0.2L:1Kg). After pyrolysis reaction at 320℃ for 5h, a high-order carbon microcrystalline petroleum coke precursor with a yield of 83% is obtained. After testing, the initial distillation point of the high-order carbon microcrystalline petroleum coke precursor is 420℃, and the density at 100℃ is 1.23g / cm 3 , asphaltene content is 20%, resin content is 19%, aromatic content is 60%, saturated content is 1%, residual carbon content is 25%, and aromatic hydrogen content is 15%.
[0099] Polymerization: The precursor of high-regular carbon microcrystalline petroleum coke and artificial graphite powder with a particle size of less than 2um are hot mixed in a screw extruder at a mass ratio of 100:1 for 40 minutes, and the obtained mixture is transported to a kettle polymerization reactor by a high-temperature mechanical pump for polymerization reaction at 510°C for 24 hours, and then cooled to room temperature to obtain high-regular carbon microcrystalline petroleum coke. According to the test, the fine mosaic structure ratio of the high-regular carbon microcrystalline petroleum coke is 90%, the carbon microcrystalline structure size is 1 to 10um, and the concentrated distribution is 1 to 3um; the volatile matter is 8%, the true density is 1.51g / cm3, the ash content is 0.006%, and the sulfur content is 0.4%.
[0100] Preparation of artificial graphite
[0101] Crushing: High-order carbon microcrystalline petroleum coke and petroleum asphalt (softening point is 200°C) are crushed and classified by mechanical grinding machines to obtain high-order carbon microcrystalline petroleum coke powder and petroleum asphalt powder. The D10, D90 and D50 of the high-order carbon microcrystalline petroleum coke powder are 3um, 11um and 7um respectively.
[0102] Mixing modification: High-regular carbon microcrystalline petroleum coke powder and petroleum asphalt powder are mixed in a conical mixer at a mass ratio of 100:1 for 30 minutes, and then heated to 700°C at a rate of 5°C / min in a reactor containing a stirring device. The coke powder surface is modified at this temperature in a mixed atmosphere of water vapor and nitrogen (the volume ratio of water vapor to nitrogen is 1:100, and the gas flow rate is 0.07L / min) for 10 hours, and then nitrogen is introduced for cooling to room temperature to obtain a modified material;
[0103] Heat treatment (carbonization + graphitization): The modified material is carbonized at 1000°C and graphitized at 3000°C in a nitrogen atmosphere, and then crushed, classified, demagnetized and screened to obtain an artificial graphite negative electrode material.
[0104] Comparative Example 1
[0105] This comparative example provides an artificial graphite negative electrode material, and the specific steps are as follows:
[0106] Cutting: Ethylene tar, catalytic cracking oil slurry and petroleum residue were mixed in a mass ratio of 70:20:10, and then vacuum distilled at a pressure of 0.66 kPa to remove light oil and collect heavy oil with an initial boiling point of 350°C. After testing, the density of the heavy oil at 15°C was 1.02 g / cm 3 , the asphaltene content is 3%, the resin content is 10%, the saturated content is 30%, the aromatic content is 57%, the sulfur content is 0.1%, the nitrogen content is 0.5%, and the residual carbon content is 10%.
[0107] Pyrolysis: The above raw materials without impurity removal were put into a stirring electromagnetic heating reactor, and heated at a stirring rate of 150r / min from room temperature at a heating rate of 5℃ / min. At the same time, nitrogen at room temperature was introduced. After pyrolysis reaction at 350℃ for 15h, a petroleum coke precursor with a yield of 52% was obtained. After testing, the initial boiling point of the petroleum coke precursor was 400℃, and the density at 100℃ was 1.22g / cm 3 , asphaltene content is 25%, resin content is 30%, aromatic content is 39%, saturated content is 6%, residual carbon content is 33%, and aromatic hydrogen content is 8%.
[0108] Polymerization: The above petroleum coke precursor and the same type of coke powder with a particle size of less than 1um are hot mixed in a screw extruder at a mass ratio of 100:20 for 30 minutes. The obtained mixture is transported to a polymerization reactor by a high-temperature mechanical pump for polymerization reaction at 550°C for 5 hours, and then cooled to room temperature to obtain petroleum coke. According to the test, the fine mosaic structure ratio of the petroleum coke is 55%, the carbon microcrystalline structure size is 1 to 60um, and is evenly distributed; the volatile matter is 5%, and the true density is 1.76g / cm 3 , the ash content is 0.3% and the sulfur content is 0.3%.
[0109] Crushing: The petroleum coke and petroleum asphalt (softening point is 180°C) are crushed and classified by a mechanical grinder to obtain petroleum coke powder and petroleum asphalt powder, wherein the D10, D90 and D50 of the petroleum coke powder are 5um, 15um and 7um, respectively;
[0110] Mixing modification: The mass ratio of the above petroleum coke powder to petroleum asphalt powder is 100:9, and after mixing in a conical mixer for 30 minutes, the temperature is raised to 670°C at a rate of 2°C / min in a reactor containing a stirring device, and the surface of the coke powder is modified at this temperature in a nitrogen atmosphere for 5 hours, and then nitrogen is introduced for cooling to room temperature to obtain a modified material;
[0111] Heat treatment (carbonization + graphitization): The modified material is carbonized at 1000°C and graphitized at 2800°C in a nitrogen atmosphere, and then crushed, classified, demagnetized and screened to obtain an artificial graphite negative electrode material.
[0112] Comparative Example 2
[0113] This comparative example provides an artificial graphite negative electrode material, and the specific steps are as follows:
[0114] Cutting: Ethylene tar, catalytic cracking oil slurry and petroleum residue were mixed in a mass ratio of 70:20:10, and then vacuum distilled at a pressure of 10kpa to remove light oil and collect heavy oil with an initial boiling point of 350℃. After testing, the density of the heavy oil at 15℃ is 1.02g / cm 3 , asphaltene content is 8%, resin content is 10%, aromatic content is 62%, saturated content is 20%, sulfur content is 0.7%, nitrogen content is 0.2%, residual carbon content is 21%, and aromatic hydrogen content is 30%.
[0115] Pyrolysis: The above raw materials without impurity removal were put into a stirring electromagnetic heating reactor, and heated at a stirring rate of 150r / min from room temperature at a heating rate of 5℃ / min. At the same time, nitrogen at room temperature was introduced. After pyrolysis reaction at 350℃ for 8h, a precursor of petroleum coke with a yield of 60% was obtained. After testing, the initial boiling point of the precursor of petroleum coke was 420℃, and the density at 100℃ was 1.23g / cm 3 , asphaltene content is 23%, resin content is 31%, aromatic content is 3%, saturated content is 10%, residual carbon content is 27%, and aromatic hydrogen content is 21%.
[0116] Polymerization: The above petroleum coke precursor is polymerized in a polymerization reactor at 510°C for 8 hours, and then cooled to room temperature to obtain petroleum coke. According to the test, the petroleum coke has a fine mosaic structure ratio of 30%, a carbon microcrystalline structure size of 1-60um, and a concentration of 20-40um; a volatile matter of 12%, and a true density of 1.73g / cm 3 , the ash content is 0.4% and the sulfur content is 1.5%.
[0117] Crushing: The petroleum coke and petroleum asphalt (softening point is 220°C) are crushed and classified by a mechanical grinder to obtain petroleum coke powder and petroleum asphalt powder, wherein the D10, D90 and D50 of the petroleum coke powder are 5um, 15um and 7um respectively;
[0118] Mixing modification: The mass ratio of the above petroleum coke powder to petroleum asphalt powder is 100:5, and after mixing in a conical mixer for 30 minutes, the surface of the coke powder is modified in a reactor with a stirring device at 650°C in a nitrogen atmosphere for 5 hours, and then nitrogen is introduced for cooling to room temperature to obtain a modified material;
[0119] Heat treatment (carbonization + graphitization): The modified material is carbonized at 1000°C and graphitized at 2800°C in a nitrogen atmosphere, and then crushed, classified, demagnetized and screened to obtain an artificial graphite negative electrode material.
[0120] The artificial graphite negative electrode materials prepared in each embodiment and comparative example were subjected to performance tests according to test method 1 and test method 2. The specific test results are shown in the following table.
[0121] Table 1
[0122]
[0123]
[0124] From the data in the above table, it can be seen that by adopting the preparation process of the highly regular carbon microcrystalline petroleum coke combined with artificial graphite provided by the present invention, the lithium battery negative electrode material has excellent comprehensive performance such as long-life energy storage and rate capability. If the raw materials, precursors and preparation process of petroleum coke are not intervened, the capacity and performance of the prepared artificial graphite decay rapidly after cycling and cannot be used in the field of energy storage.
[0125] Figure 1 This is a polarized photo of the highly regular carbon microcrystalline petroleum coke obtained in Example 1. Figure 3 and Figure 4 They are polarized photos of petroleum cokes prepared in Comparative Example 1 and Comparative Example 2, respectively. Figure 1 and Figure 3 and Figure 4 By comparison, it can be seen that the petroleum coke prepared from traditional heavy oil raw materials will have a certain amount of streamline and fiber structure generated without the modulation of the precursor and the adjustment of the formation of carbon microcrystals during the pyrolysis process. In addition, the high impurity content will generate some structures without polarization characteristics, which will reduce the electrochemical performance of future artificial graphite. Figure 2 is a polarized photo of the highly regular carbon microcrystalline petroleum coke obtained in Example 2. Figure 1 and Figure 2 From the comparison, it can be seen that the yield of petroleum coke can be changed by fine-tuning the raw material composition, changing the precursor and the pyrolysis process within a certain range, and the structure of petroleum coke basically maintains a relatively stable distribution.
[0126] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A high-structured carbon microcrystalline petroleum coke, characterized in that: The fine mosaic structure ratio of the highly regular carbon microcrystalline petroleum coke is greater than or equal to 90%; the carbon microcrystalline structure size is 1 to 10 um, concentrated in 3 to 8 um; the volatile content is 5% to 15%; the true density is 1.4 to 1.6 g / cm 3 ; The ash content is 0.001%~0.02%; the sulfur content is 0.5%~1%.
2. A method for preparing high-structured carbon microcrystalline petroleum coke according to claim 1, characterized in that: The steps include: Cutting: Cutting the light oil from the crude oil to get the heavy oil; Impurity removal: passing the heavy oil into a composite flow field of an electrostatic field and a gravity field for purification to obtain a high-regular carbon microcrystalline petroleum coke precursor raw material; Pyrolysis: Under stirring, the high-order carbon microcrystalline petroleum coke precursor raw material is subjected to pyrolysis reaction with oxygen-containing gas to obtain a high-order carbon microcrystalline petroleum coke precursor; Polymerization: The precursor of the high-regular carbon microcrystalline petroleum coke is thermally mixed with the carbonaceous micropowder, and the obtained mixture is subjected to polymerization reaction to obtain the high-regular carbon microcrystalline petroleum coke.
3. The preparation method according to claim 2, characterized in that: The raw oil is selected from at least one of catalytic cracking slurry, ethylene tar, coker wax oil, thermal cracking residue, hydrogenation tail oil, furfural extracted oil, reformed heavy aromatic oil, ester refined solvent extracted lubricating oil and deasphalted oil of vacuum residue.
4. The preparation method according to claim 2, characterized in that: In the cutting step, the light oil is distilled and cut off at 0.6-2.7 kPa, and the initial distillation point of the heavy oil is 240-350°C, preferably 250-340°C, and more preferably 260-330°C.
5. The preparation method according to claim 4, characterized in that: In the cutting step, the density of the heavy oil obtained at 15°C is 0.9-1.1 g / cm 3 ; The asphaltene content is 0-20%, the gum content is 0-18%, the aromatic content is 60%-90%, the saturated content is 10%-30%, the sulfur content is 0.1%-2%, the nitrogen content is 0.1%-1%, and the ash content is 100-2000ppm.
6. The preparation method according to claim 2, characterized in that: In the impurity removal step, the intensity of the electrostatic field is 1×10 5 ~10×10 5 V / m, preferably 2×10 5 ~8×10 5 V / m; The flow rate of the heavy oil passing into the composite flow field of the electrostatic field and the gravity field is 0.0001-0.001 m / s, preferably 0.0005-0.0008 m / s.
7. The preparation method according to claim 6, characterized in that: In the impurity removal step, the obtained high-regular carbon microcrystalline petroleum coke precursor raw material has an asphaltene content of 0-5% and an ash content of 0-5 ppm.
8. The preparation method according to claim 2, characterized in that: In the pyrolysis step, the mass volume ratio of the high-structured carbon microcrystalline petroleum coke precursor raw material to the oxygen-containing gas is 1 kg: (0.2-2) L, preferably 1 kg: (0.5-1.5) L; the temperature of the oxygen-containing gas is 100-300° C., preferably 150-250° C.; and / or The oxygen-containing gas is selected from air, or a mixture of oxygen and an inert gas, wherein the inert gas is any one or more of nitrogen, argon and helium; more preferably, the oxygen-containing gas is a mixture of oxygen and an inert gas, wherein the volume ratio of the oxygen to the inert gas in the mixture of oxygen and the inert gas is 1:3 to 1:5; and / or The temperature of the pyrolysis reaction is 280-380°C, preferably 300-320°C; the time of the pyrolysis reaction is 1-10h, preferably 3-5h; the stirring rate is 50-200r / min, preferably 100-150r / min; the heating rate is 10-30°C / min, preferably 15-25°C / min.
9. The preparation method according to claim 8, characterized in that: In the pyrolysis step, the precursor of the high-regular carbon microcrystalline petroleum coke has an initial boiling point of 360-420°C, preferably 380-400°C; and a density of 1.1-1.3 g / cm 3 ; Asphaltene content is 1% to 20%, gum content is 1% to 20%, aromatic content is 50% to 70%; saturated content is 1% to 5%; residual carbon content is 20% to 30%, preferably 22% to 25%; aromatic hydrogen content is 10% to 25%, preferably 15% to 20%.
10. The preparation method according to claim 2, characterized in that: In the polymerization step, the mass ratio of the precursor of the high-regular carbon microcrystalline petroleum coke to the carbonaceous micropowder is 100:1 to 100:20, preferably 100:5 to 100:10; and / or The carbonaceous powder is selected from at least one of needle coke powder, pitch coke powder, isotropic coke powder, artificial graphite powder and fine powder produced during the preparation of artificial graphite; the carbonaceous powder has a particle size of less than 5um, preferably less than 3um, more preferably less than 2um; and / or The polymerization reaction temperature is 450-550°C, the reaction time is 5-36h, preferably 12-24h; and / or The heat mixing method is a pipeline mixer, preferably a kneader or a screw extruder; the heat mixing time is 30 to 60 minutes.
11. A method for preparing an artificial graphite negative electrode material, characterized in that: The steps include: Crushing: crushing the high-structured carbon microcrystalline petroleum coke and the modifier separately; Mixing modification: After the above-mentioned crushed high-regular carbon microcrystalline petroleum coke is mixed with the crushed modifier, surface modification is performed in an oxygen-containing nitrogen atmosphere to obtain a modified material; Heat treatment: subjecting the modified material to carbonization and graphitization treatments in sequence in an inert atmosphere to obtain an artificial graphite negative electrode material; Wherein, the high-structured carbon microcrystalline petroleum coke is the high-structured carbon microcrystalline petroleum coke described in claim 1 or the high-structured carbon microcrystalline petroleum coke prepared by the preparation method of the high-structured carbon microcrystalline petroleum coke described in any one of claims 2 to 10.
12. The method for preparing the artificial graphite negative electrode material according to claim 11, characterized in that: In the pulverizing step, the D10 of the pulverized high-regular carbon microcrystalline petroleum coke is 1 to 5 um, preferably 2 to 4 um; the D90 is 9 to 15 um, preferably 10 to 12 um; the D50 is 5 to 8 um, preferably 6 to 7 um; and / or The modifier is a precursor of petroleum asphalt, coal-based asphalt powder or high-regular carbon microcrystalline petroleum coke with a softening point greater than 150°C.
13. The method for preparing the artificial graphite negative electrode material according to claim 11, characterized in that: In the mixing and modification step, the mass ratio of the crushed high-regular carbon microcrystalline petroleum coke to the crushed modifier is 100:1 to 100:15, preferably 100:7 to 100:9; and / or The mixing time of the crushed high-regular carbon microcrystalline petroleum coke and the crushed modifier is 30 to 60 minutes, preferably 40 to 50 minutes; and / or The oxygen-containing nitrogen atmosphere is a mixed gas of oxygen-containing gas and nitrogen, the volume ratio of the oxygen-containing gas to the nitrogen is 1 to 10:100, preferably 4 to 6:100, the oxygen-containing gas is selected from water vapor, carbon dioxide, air, or a mixed gas of pure oxygen and an inert gas, and the inert gas is selected from nitrogen, helium or argon; and / or During the surface modification process, the flow rate of the oxygen-containing nitrogen is 0.01 to 0.3 L / min, preferably 0.05 to 0.1 L / min, the surface modification temperature is 550 to 700°C, preferably 620 to 670°C; the surface modification time is 5 to 15 h, preferably 6 to 10 h, and the heating rate is 1 to 10°C / min, preferably 5 to 7°C / min.
14. The method for preparing the artificial graphite negative electrode material according to claim 11, characterized in that: In the heat treatment step, the carbonization temperature is 800-1100°C, and the graphitization temperature is 2700-3000°C.
15. The artificial graphite negative electrode material obtained by the method for preparing the artificial graphite negative electrode material according to any one of claims 11 to 14, characterized in that: The D50 of the artificial graphite negative electrode material is 10 to 22 um, preferably 12 to 18 um.
Citation Information
Cited By
Preparation method of petroleum coke-based high-tap-density artificial graphite
CN121591209A
